Upaya Guru Dalam Mengimplementasikan Nilai-Nilai Karakter Pada Mata Pelajaran PPKN Melalui Pendekatan Kontekstual Terhadap Siswa Di Min 12 Kota Medan - Dinda May Sarah; Muhammad Basri; Zunidar (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
This study aims to determine the efforts and influence of the application of character values in Civics subjects through a contextual approach to students at MIN 12 Medan. This research methodology uses classroom action research methods. This research was conducted at MIN 12 Medan City, Medan Tembung District. The sample in this study consisted of 1 class, namely class V-C. Data collection in this study used test results in the form of a questionnaire. The results of this study indicate that teachers make a special approach to students and parents of students in order to work together in educating their children, teachers also constantly motivate and advise students to behave well and provide a deterrent effect for students who still violate the rules, and far from behaving well, such as giving sanctions. Based on the results of the study, it shows that there is an influence in the application of character values on the contextual approach which can be seen from the results of the analysis of the average significant value in cycle I obtained by 63% with a fairly well developed category. Meanwhile, in cycle II it was obtained at 80% with a very well developed category.